ANALISIS RANTAI PASOK BUNGA SEDAP MALAM (Polianthes tuberosa) DI KECAMATAN AMBARAWA - Afif Nur Zahidah; W. Roessali; A. Setiadi (University of Jember, 2020)
The purpose of this research is to find out the description of performance of the supply chain and analyze the marketing channels for Polianthes tuberosa based on margin calculation and marketing efficiency. The research method used was a survey. Respondents consisted of farmers and actors at the flower marketing agency as well as night. Polianthes tuberosa farmers in Baran Village who were respondents as many as 26 and the number of samples of marketing institutions as many as 30 people consisting of market traders, florists and consumers. The data analysis method used is descriptive qualitative and quantitative based on the supply chain development method in the Asian Productivity Organization (APO). The results of the study show that supply chain performance can be said to be quite good, marked by the fulfillment of demand for Polianthes tuberosa interest to consumers. Clear and directed supply chain goals, good supply chain structure, good supply chain management, sufficient and adequate resources and overall good supply chain performance. There are 3 marketing channels that are already efficient with the value of farmer share in marketing channel I that is 50.19%, marketing channel II which is 50.19% and marketing channel III which is 77.21%.